Design of 20 W fiber-coupled green laser diode by Zemax *Project supported by the National Key R& D Program of China (No. 2016YFB0402105), the Key Deployment Program of the Chinese Academy of Sciences (No. KGZD-SW-T01-2), and the National Natural Science Foundation of China (No. 61404135). (September 2017) - Qi, Yunfei; Zhao, Pengfei; Wu, Yulong; Chen, Yongqi; Zou, Yonggang
Abstract: We represent a design of a 20 W, fiber-coupled diode laser module based on 26 single emitters at 520 nm. The module can produce more than 20 W output power from a standard fiber with core diameter of 400 μ m and numerical aperture (NA) of 0.22. To achieve a 20 W laser beam, the spatial beam combination and polarization beam combination by polarization beam splitter are used to combine output of 26 single emitters into a single beam, and then an aspheric lens is used to couple the combined beam into an optical fiber. The simulation shows that the total coupling efficiency is more than 95%.